Analysis of Consumer Behavior with Financial Technology as a Moderating Variable among Students of Universitas Pembangunan Nasional Veteran Jawa Timur - Vindi Atika Fatmawati; Rahman Amrullah Suwaidi (Universitas KH. Abdul Chalim Mojokerto, 2025)
Consumptive behavior is an action related to the decision to buy, but does not involve the thought process in making purchasing decisions. The purpose of this study is to analyze the factors that influence consumptive behavior and its implications for individual financial management, especially students of UPN Veteran East Java. This study uses a quantitative method with primary data collected through Google Form. The data analysis technique used is stratified random sampling with data analysis tests using the Structural Equation Model - Partial Least Square (SEM-PLS) analysis technique with SmartPLS software version 4.0. The results of this study indicate that lifestyle variables are able to contribute to consumptive behavior positively and significantly, financial literacy is able to contribute to consumptive behavior negatively and significantly, financial technology is able to contribute lifestyle to consumptive behavior, while financial technology is not able to contribute financial literacy to consumptive behavior.